Two new species of Begonia from Andean Peru - Moonlight, P.w.; Reynel, C. (Phytotaxa, 2018)
Two new species of Begonia from montane forests in Andean Peru are described and illustrated as B. lamolina and B. amoeboides. These two species are placed within B. section Cyathocnemis and are morphologically most similar to B. lophoptera, which is lectotypified, and a new description is provided. Preliminary IUCN Red List assessments are provided for all three species.